Predatory capacity of Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) on Brevipalpus phoenicis (Geijskes, 1939) (Acari: Tenuipalpidae) - Silva, Rogério Antônio; Reis, Paulo Rebelles; Carvalho, César Freire; Souza, Brígida (Coffee Science - ISSN 1984-3909, 2007)
Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) is present naturally in many plants, as a natural enemy with a high predatory potential. The mite Brevipalpus phoenicis (Geijskes, 1939) (Acari: Tenuipalpidae) is a polyphagous pest and is the vector of the coffee ring spot virus in coffee plants. This work was made to evaluate the predatory capacity of C. externa larvae on B. phoenicis through bioassays. The experiments were done under laboratory conditions, using 3-cm diameter arenas made up of Catuai coffee leaves (Coffea arabica L.). Fifty mites were placed in each arena for each development phase and green lacewing larva (1st 2nd and 3rd instar), with 16 replicates. The evaluation period was of 4 hours. First instar larvae showed better predatory capacity when compared to those of second and third instars regardless the mite developmental stage. Preference of first instar larvae of C. externa was for eggs, followed by larvae, nymphs and finally by adults of B. phoenicis. Therefore, results indicate that larvae of C. externa can act as an auxiliary organism in regulating B. phoenicis populations in coffee trees agroecosystems.